Utilization pattern and controlling system of antibiotics in tertiary care hospital in Nepal. - Alam, Kadir (2011)
ABSTRACT: Antibiotic policy in many developed countries reported to be successful in reducing the irrational use of antibiotics and antibiotic resistance. The study was aimed to study utilization of antibiotics and understand the controlling system of antibiotics at tertiary care hospitals in Nepal using Donabedian model of quality of medical care. Combinations of quantitative and qualitative methods were used in this study. Utilization pattern of antibiotics revealed that about 44% and 29% of admitted patients received antibiotics in Western Regional Hospital (WRH) and Manipal Teaching Hospital (MTH) with the mean number of antibiotics 2.25±1.14 and 1.84±0.915 respectively. Overall, antibiotic use in WRH (68.45 DDD/100 bed-days) was 3 fold higher than MTH (22.21 DDD/100 bed- days). The mean cost of antibiotics was NRs. 1007.78 ($14) in WRH and NRs. 892.88 ($12.8) in MTH. E. coli showed 100% resistance to Nalidixic acid, Erythromycin, Cotrimoxazole and Cephalexin in WRH. About 40% and 32% of treatment of enteric fever were inappropriate in WRH and MTH respectively. Structure components ( Organizational, Personnel, Policy or guideline and Surveillance) were slightly better in the private hospitals than public hospitals because of existence of semi-functional and scattered policy and guideline. Process components were also relatively better in private hospitals because of good prescribing process and existence of their own hospital pharmacy. The study found the huge communication gap between healthcare professionals on National Surveillance program and lack of awareness on national drug policy. Hence, we strongly recommend the implementation of antibiotic policy recommended by the expert well as national drug policy. We also recommend the proper compilation and dissemination of national surveillance data. Keywords: Antibiotics Utilization / Controlling System / Antibiotic Policy / Rational Use of Medicine / Nepal